Diversidade genética e constituição química dos óleos essenciais de populações de Lychnophora ericoides mart. e Lychnophora pinaster Mart - Vieira, Maria Aparecida Ribeiro [UNESP] (2012)
Lychnophora ericoides and Lychnophora pinaster are endemic Brazilian medicinal species used in popular medicine as an analgesic and anti-inflammatory for treating bruises and rheumatism. This study considered the genetic characterization and chemical composition of the essential oils of three populations of L. ericoides (P1 - São Roque de Minas and P2 and P3 - Capitólio), and two populations of L. pinaster (P4 - Olhos D'Água and P5 - Estrada de Diamantina), collected in the State of Minas Gerais. The essential oils were extracted by hydro-distillation and the characterization of the chemical composition was performed by gas chromatography-mass spectrometry. The characterization of the genetic diversity was made using molecular microsatellite marker. The major substances of the essential oils from L. ericoides of P1-population were γ-eudesmol, α-muurolol and α-eudesmol and P2- and P3-population were terpinen-4-ol, β-atlantol and orto-acetoxy-bisabolol. The main substances of the species L. pinaster of P4-population were 14-hydroxy-Z-caryophyllene and an oxygenated sesquiterpene and of P5-population were 14-hydroxy-α-humulene and α- humulene-14-oic acid. The average value of the heterozygosity observed (HO) and expected (HE) were 0.297 and 0.406 for L. ericoides, and 0.222 and 0.307 for L. pinaster, respectively. The genetic variability was higher within populations for both species, however populations of L. ericoides also presented high diversity among the populations (FST = 0.370), while populations of L. pinaster presented low variability among populations (FST = 0.014). The AMOVA analysis between groups of populations separated by species was 9%, suggesting crossing between the species. The cluster analysis highlighted the formation of two groups:...